KEPRIBADIAN TOKOH UTAMA WANITA DALAM NOVEL ALISYA KARYA MUHAMMAD MAKHDLORI: KAJIAN PSIKOLOGI SASTRA - Fajriyah, Khoiriyatul; Mulawarman, Widyatmike Gede; Rokhmansyah, Alfian (Fakultas Ilmu Budaya, Universitas Mulawarman, 2017)
The purposes of this research are to describe story facts, personality structure of female lead character, and the factor behind personality changes of female lead character in the novel Alisya by Muhammad Makhdlori. This research is a descriptive qualitative research with psychology of literature studies. This research use objective approach. The data source of this research is from the novel Alisya by Muhammad Makhdlori. The data collection techniques are reading and noting. The data analysis technique used qualitative analysis that consists of three ways, those are data reduction, data presentation, and drawing conclusion. The results of this research showed some findings, firstly, story fact in the novel Alisya consists of plot, characterization, and setting. The plot in this novel is forward. The characters in this novel are having roles as main character and additional character. Settings of place in this novel are in Batam, Jakarta and Singapore. Settings of time happen before Alisya became a bitch, after Alisya became a bitch, when Alisya infected HIV’s virus and the last when Alisya stop became a bitch. Social setting in this novel is society’s point of view of HIV’s victim. Secondly, the stimulus of id in Alisya portrayed when Alisya want to flee from poverty, want to become a famous model, want to take a break, want to die, and want to eat. The responds of ego showed when Alisya decided to achieve an offer to take naked photo in magazine and when she decided to achieve Sandy’s invitation to go to the party that held in Singapore. The superego responds showed when Alisya counterbalances whether to achieve the offer to take naked photo or not. Thirdly, from the analysis of Alisya’s personality the researcher fond some factors of Alisya’s personality changes, those are; physical factor, social factor, and the factor from her own self.Keywords: female lead character, personality, Alisya novel